Fiber Separation from Ground Corn Flour Using an Electrostatic Method. Issue 6 (20th November 2013) - Pandya, Tejas S.; Srinivasan, Radhakrishnan; Thompson, Courtney Paige
ABSTRACT: Corn kernels contain 9% fiber by weight, which is not digested well by nonruminants such as chicken and swine. Also, fiber is nonreactive in the dry‐grind process for ethanol production and is considered as feedstock for the production of second‐generation bioethanol. Fiber separation can enhance starch concentration in animal feed and increase starch loading in ethanol plants. Electrostatic separation is used to separate particles from granular mixtures under the influence of electrical forces. The Elusieve process, a combination of sieving and air classification, separates fiber by taking advantage of differences in size, shape, and density. Differences in dielectric properties could also be exploited for fiber separation. The aim of this study was to evaluate the effectiveness of electrostatic separation of fiber particles from corn. When the electrostatic method was used in conjunction with Elusieve processing, the fiber product had higher neutral detergent fiber (NDF, 52.9%) compared with Elusieve processing alone (NDF of 40.5%). Also, a higher quantity of enhanced flour (95.0% yield) was produced when the electrostatic method was used in conjunction with Elusieve processing compared with Elusieve processing alone (93.0% yield), without any change in quality of the enhanced flour (NDF of 6.6% in both cases). The electrostatic method improved fiber separation when used in conjunction with Elusieve processing.